ROLE OF PHYSICAL ACTIVITY IN PARKINSON’S DISEASE PREVENTION AND MANAGEMENT – A LITERATURE REVIEW - Jakub Zajączkowski,; Adrianna Zajączkowska,; Kacper Stępniak,; Jan Wilk,; Radosław Kuźma,; Karolina Marrodán-Wojtczak,; Aleksandra Kujawa,; Paulina Krzeszowska,; Karolina Krochmal,; Jakub Jarmołowicz, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Parkinson’s disease (PD) is a progressive neurodegenerative disorder that is characterized by both motor and non-motor symptoms, such as bradykinesia, tremor, rigidity and instability of the posture. Millions of people suffer from the disease around the world, affecting not only the patients, but also public health systems. Pharmacological interventions exist, although aside from reducing symptoms, no drugs that stop the progression of PD have been developed.That is why interventions from outside the realm of pharmacology have garnered increased focus of the academics, one of them being physical activity. In recent years, an extensive research was done to prove or disprove a link between exercise and PD’s prevention and management.What this study aims to do, is to comprehensively gather and review current state of literature in the field of physical activity’s role in prevention and management of Parkinson’s disease.Material and methods: Our method of research was to scan the databases of academic articles easily accessible on the Internet, such as PubMed, Google Scholar and others. Our team searched for “Parkinson’s disease” together with various terms, such as “physical activity”, “exercise”, “prevention”, “management”, “symptoms” and “treatment”. Following that, the obtained data were manually analysed.Conclusions: This review, based on quoted research, points to physical activity as a valuable addition to the standard pharmacological treatments, with its potentially beneficial effects all across the PD’s development timeline. From disease prevention and modification, to management of the symptoms, both motor and non-motor alike.Additional research ought to be conducted in the field to explain the mechanisms and to maximize the effect of the interventions. Nevertheless, contemporary state of knowledge heavily suggests incorporating physical activity into standard treatment strategies for Parkinson’s disease.